Study on the Effects of a π Electron Conjugated Structure in Binuclear Metallophthalocyanines Graphene-Based Oxygen Reduction Reaction Catalysts - Gai Zhang; Bulei Liu; Yufan Zhang; Tiantian Li; Weixing Chen; Weifeng Zhao (Nanomaterials, 2020)
The high overpotentials for oxygen reduction reaction (ORR) create an extremely negative impact on the energy efficiency of the air-based battery systems. To overcome this problem, binuclear ball-type metallophthalocyanines containing methoxy substituents (M2Pc2(EP)4, M = Fe(II), Co(II) and Zn(II)) were wrapped with polystyrene sodium sulfonate (PSS) modified graphene oxide (GO), using a facilely “solvothermal π-π assembly” method to prepare M2Pc2(EP)4/PSS-Gr composites. Compared with the commercial Pt/C catalysts, the M2Pc2(EP)4/PSS-Gr composites enhanced the catalytic activity of oxygen reduction reaction. The π electron conjugated structure of the MN4-type phthalocyanine macrocyclic system strongly influenced the one-step four-electron electrocatalytic process of the M2Pc2(EP)4/PSS-Gr composites. Moreover, the π-π interactions between the M2Pc2(EP)4 and PSS-Gr dramatically enhanced the π electron density in the conjugated structure and oxygen could be reduced more easily. The electrocatalytic activity test was displayed in the order of Fe2Pc2(FP)4/PSS-Gr > Co2Pc2(EP)4/PSS-Gr > Zn2Pc2(EP)4/PSS-Gr. The results indicated that the catalytic performance of M2Pc2Rn could be enhanced by the modification of π electron conjugated structure of M2Pc2(EP)4 and carbon materials.